2021
DOI: 10.4269/ajtmh.20-1444
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Human Herpes Viruses in Suspected Measles Serum Samples from Senegal, 2014 to 2017

Abstract: Herpesviruses are known to cause a diversity of clinical syndromes, ranging from minor cutaneous lesions to life-threatening illnesses, especially in immunocompromised hosts. Here, we investigate retrospectively the contribution of five human herpesviruses, including herpes simplex virus Cytomegalovirus (CMV), the Epstein–Barr virus (EBV), human herpesvirus 6, and varicella zoster virus (VZV) in serum samples collected from measles suspected patients with at least fever and rash. Sera specimens were first test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The case-finding criteria are broad to maintain surveillance sensitivity and atypical cutaneous rashes may also be included. In a previous study it was shown that among 3358 measles suspected patients collected between 2012 and 2017, 52.5% were attributable to human herpes viruses, with varicella zoster virus (VZV) being the most commonly detected (44.3%), whereas only 6.7% and 4.5% were positive for measles and rubella IgM, respectively [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The case-finding criteria are broad to maintain surveillance sensitivity and atypical cutaneous rashes may also be included. In a previous study it was shown that among 3358 measles suspected patients collected between 2012 and 2017, 52.5% were attributable to human herpes viruses, with varicella zoster virus (VZV) being the most commonly detected (44.3%), whereas only 6.7% and 4.5% were positive for measles and rubella IgM, respectively [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tests are performed in singleplex using the specific primers and probe for each virus. The TaqMan Universal PCR Master Mix kit (Applied Biosystems, Waltham, MA, USA) is used for real time amplifications, as previously reported [ 21 ].…”
Section: Methodsmentioning
confidence: 99%